MOF-templated synthesis of 3D Bi2O3 supracrystals with bcc packing. Issue 36 (4th September 2018) - Guo, Wei; Hassan, Zeinab M.; Kübel, Christian; Haldar, Ritesh; Weidler, Peter G.; Heissler, Stefan; Peikert, Katharina; Fröba, Michael; Redel, Engelbert; Wöll, Christof
Abstract : We describe a non-conventional, MOF-based approach with modified linkers to fabricate 3D Bi2 O3 supracrystals. Abstract : We describe a non-conventional, MOF-based approach with modified linkers to fabricate 3D Bi2 O3 supracrystals. The nanoparticle (NP) assembly exhibits bcc-packing, which is difficult to achieve with other methods. The NPs possess a very narrow size distribution. The individual NPs were synthesized inside the pores of a surface-mounted metal–organic framework (SURMOF) template via a photo-decomposition procedure. The supracrystals were thoroughly characterized using X-ray diffraction (XRD), infrared (IR) and Raman spectroscopy as well as high-resolution transmission electron microscopy (HR-TEM) and SAED (Selected Area Electron Diffraction). In order to achieve sharp size distributions of the NPs, the pores within the SURMOF were functionalized with amino (–NH2 ) functional groups acting as nucleation centers. MOFs lacking such additional functionalities, Cu3 (BTC)2, yielded much broader size distributions. These findings provide a unique molecular design tool for creating nanometer-sized reaction compartments for the synthesis of supracrystals with packing types not accessible via self-assembly.